2009
DOI: 10.1128/jb.00532-09
|View full text |Cite
|
Sign up to set email alerts
|

Thioredoxin 1 Participates in the Activity of theSalmonella entericaSerovar Typhimurium Pathogenicity Island 2 Type III Secretion System

Abstract: The facultative intracellular pathogen Salmonella enterica serovar Typhimurium relies on its Salmonella pathogenicity island 2 (SPI2) type III secretion system (T3SS) for intracellular replication and virulence. We report that the oxidoreductase thioredoxin 1 (TrxA) and SPI2 are coinduced for expression under in vitro conditions that mimic an intravacuolar environment, that TrxA is needed for proper SPI2 activity under these conditions, and that TrxA is indispensable for SPI2 activity in both phagocytic and ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 57 publications
1
19
0
Order By: Relevance
“…These investigations indicate that thioredoxin-1 does not depend on its well-characterized thiol-disulfide oxidoreductase to support SPI2 expression needed for the intracellular growth of Salmonella . These findings are consistent with previous published work that showed a role for TrxA in regulation of SPI2 function (Negrea et al, 2009). We also tested the survival of Salmonella expressing wild-type trxA or the trxA C32A C35A variant in primary macrophages producing large amounts of ROS through the enzymatic activity of the NADPH phagocyte oxidase (Fig.…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…These investigations indicate that thioredoxin-1 does not depend on its well-characterized thiol-disulfide oxidoreductase to support SPI2 expression needed for the intracellular growth of Salmonella . These findings are consistent with previous published work that showed a role for TrxA in regulation of SPI2 function (Negrea et al, 2009). We also tested the survival of Salmonella expressing wild-type trxA or the trxA C32A C35A variant in primary macrophages producing large amounts of ROS through the enzymatic activity of the NADPH phagocyte oxidase (Fig.…”
Section: Resultssupporting
confidence: 94%
“…By directing electrons from NADPH and thioredoxin reductase to disulfide bonds in target proteins, thioredoxins maintain thiol redox homeostasis. Regulation of SPI2 expression by thioredoxin-1 is critical to Salmonella pathogenesis (Bjur et al, 2006; Negrea et al, 2009), but the molecular mechanism by which thioredoxin-1 promotes SPI2 expression and Salmonella virulence is incompletely understood. The classical oxidoreductase activity of thioredoxin-1 promotes antioxidant defenses of Salmonella in vitro , but appears to be largely dispensable in vivo .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Salmonella and E. coli have two major redox systems to repair oxidized sulfhydryl groups in cytosolic proteins, namely the thioredoxin and glutathione/ glutaredoxin systems (Stewart et al, 1998). Previous studies have uncovered a link between the expression of thioredoxin 1 (TrxA) and Salmonella virulence, as a trxA deletion strain displayed a virulence defect in BALB/c mice and a cell culture model of murine macrophage-like cells (Bjur et al, 2006;Negrea et al, 2009). In the same work deletion of grxA was found to increase fitness of Salmonella in the macrophage model (Bjur et al, 2006).…”
Section: Rewiring the Regulatory Network Of Virulence Gene Expressionmentioning
confidence: 99%
“…The trxA mutant was attenuated for virulence when injected intraperitoneally into BALB/c mice in competition experiments at a 1:1 ratio with the wild-type parent strain, unlike trxC or trxB mutants in similar experiments, showing that Trx1 contributes to the virulence of S. Typhimurium (2). Negrea et al (29) have recently reported that thioredoxin 1 is required for the proper activity of the Salmonella pathogenicity island (SPI2) type III secretion system. However, these authors did not investigate the pathology caused by infection with a trxA mutant or whether the mutant offered protection against subsequent wild-type challenge.…”
Section: ؉ T Cells and B Lymphocytes In The Spleen And Reduced Infiltmentioning
confidence: 99%